Celluloid Angels: a research study of nurses in feature fils 1900 - 2007 - Stanley, David (Blackwell Publishing Ltd, 2008)
This paper is a report of a study examining the influence on how nursing and nurses are portrayed in feature films made between 1900 and 2007, with a nurse as their main or a principle character and a story-line related specifically to nursing. Nurses and the nursing profession are frequently portrayed negatively or stereotypically in the media, with nurses often being portrayed as feminine and caring but not as leaders or professionals capable of autonomous practice. For the period from 1900 to 2007, 280 relevant films were identified. Most films were made in the United States of America of United Kingdom, although in recent years films have been increasingly produced in other countries. Early films portrayed nurses as self-sacrificial heroines, sex objects and romantics. More recent films increasingly portray them as strong and self-confident professionals.Nurse-related films offer a unique insight into the image of nurses and how they have been portrayed. Nurses need to be aware of the impact the film industry has on how nurses and nursing are perceived and represented in feature films